Economic impact of COVID-19 on tourism and remittances: Insights from Egypt - Breisinger, Clemens; Latif, Abla Abdel; Raouf, Mariam; Wiebelt, Manfred (International Food Policy Research Institute, 2020)
Using the SAM multiplier model for Egypt, we simulate the individual and combined effects of a collapse in the tourism sector and reductions in Suez Canal revenues and in foreign remittances under more and less pessimistic scenarios. SAM multiplier models are well-suited to measuring short-term direct and indirect impacts of unanticipated, rapid-onset demand- or supply-side economic shocks such as those caused by the COVID-19 pandemic. We model the demand shocks as the anticipated reductions in tourism, Suez Canal, and remittances revenues.